The crocodile is coming! - Crebbin, June; Grey, Mini (Walker Books Ltd. London, 2005)
This collection brings together over 50 poems exploring the young child's world and experience, both real and imaginary. Varied in tone - from funny to lyrical and emotional - they cover a range of poetic forms and all have June Crebbin's sure touch